Future Constructions in the Medieval South Slavonic Translations of Vita Antonii Magni - Petrov, Ivan P. (Studia Ceranea, 2022)
This paper aims at systemising the observations on the constructions used for expressing Future tense in the three known Old Slavonic translations of Vita Antonii Magni by Athansius Alexandrinus. The text was first translated in the early Old Church Slavonic period, while two other (Middle Bulgarian) translations were written in ca. 14th century. This makes the text suitable for observing the different strategies for expressing Future tense, both regarding the translation technique and its dynamics on a synchronic level, i.e., vis-à-vis other translations from the period, and from a diachronic perspective, i.e., paying closer attention to the discrepancies between the three translations themselves. The paper focuses on the Future periphrastic constructions used in the three Slavonic translations of the Life of St Anthony the Great by Athanasius of Alexandria. The approach is based on the relation with the Greek Vorlage, thus analysing closely the situation attested in the Greek original. Observations are made regarding the usage of the periphrases in the Slavonic texts adducing comparative material for similar phenomena from other early (Preslavian) and Middle Bulgarian texts. Some examples provided, as well as those from other texts, might suggest that the Old Church Slavonic periphrases were used not only to express Future tense per se, but for every non-Indicative (or non-factual) Present.